2011
DOI: 10.1107/s1600536811006039
|View full text |Cite
|
Sign up to set email alerts
|

(E)-Ethyl 2-cyano-3-[4-(4,5-diphenyl-1H-imidazol-2-yl)phenyl]acrylate dihydrate

Abstract: In the title compound, C27H21N3O2·2H2O, the three benzene rings attached to the heterocyclic imidazole ring are not coplanar with the latter, making dihedral angles of 14.8 (2), 31.4 (2), and 37.5 (2)°, respectively, for the benzene ring planes in the 2-, 4- and 5-positions. In the crystal, there are two water mol­ecules which serve as connectors between the acrylate mol­ecules and stabilize the structure via N—H⋯O, O—H⋯N, C—H⋯O and O—H⋯O hydrogen bonding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Meantime, it was found that these kinds of compounds are ubiquitous in various bioactive molecules having antiulcer, antiviral, anticancer and antihypertension properties . Although heterocyclic imidazole derivatives have been widely studied in chemistry, biology and materials science, the design and synthesis of compounds possessing a large conjugated system with high fluorescent performances is still highly desirable .…”
Section: Introductionmentioning
confidence: 99%
“…Meantime, it was found that these kinds of compounds are ubiquitous in various bioactive molecules having antiulcer, antiviral, anticancer and antihypertension properties . Although heterocyclic imidazole derivatives have been widely studied in chemistry, biology and materials science, the design and synthesis of compounds possessing a large conjugated system with high fluorescent performances is still highly desirable .…”
Section: Introductionmentioning
confidence: 99%